2008
DOI: 10.1258/la.2007.007080
|View full text |Cite
|
Sign up to set email alerts
|

Normative data of multifrequency tympanometry in rabbits

Abstract: SummaryIn an experimental study, we evaluated acoustic immittance in rabbits in order to use these data as normative values for further experimental investigations. This study is the first experimental evaluation of both conventional 226 Hz and multifrequency tympanometry (MFT) in rabbits. For the investigation, we used 33 female New Zealand rabbits weighing 3.2 -4.4 kg and aged six months. Bilateral measurements using conventional 226 Hz and MFT were performed under general anaesthetic. A 226 Hz tympanogram w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…39 Especially the middle ear is a convenient location for carrying out animal studies which poses only limited strain for the animals and offers a control at hand, namely the other ear which is usually left untreated. [40][41][42] The combination of a mesoporous silica layer on a Bioverit s II again has to be tested for biocompatibility. Corresponding cell culture tests showed that the surface covered with nanoporous silica is somewhat less bioactive than the plain uncoated, highly ''bone-friendly'' Bioverit material.…”
Section: Biocompatibility Testsmentioning
confidence: 99%
“…39 Especially the middle ear is a convenient location for carrying out animal studies which poses only limited strain for the animals and offers a control at hand, namely the other ear which is usually left untreated. [40][41][42] The combination of a mesoporous silica layer on a Bioverit s II again has to be tested for biocompatibility. Corresponding cell culture tests showed that the surface covered with nanoporous silica is somewhat less bioactive than the plain uncoated, highly ''bone-friendly'' Bioverit material.…”
Section: Biocompatibility Testsmentioning
confidence: 99%